Sir Sayyid Ahmad Khan’s Theological Thought and Its Selective Reception in Contemporary Indonesian Pesantren - Agil Shodiki Manurung (Islamic Thought Review, 2025)
This article aims to examine the theological thought of Sir Sayyid Ahmad Khan (1817–1898), a prominent nineteenth-century Muslim reformer from India, and to analyze its relevance and reception within contemporary Indonesian pesantren. While previous studies often emphasize the influence of Islamic modernism on Muslim educational reform, this study argues that pesantren engagement with Sir Sayyid’s thought is neither linear nor uncritical. Using a conceptual-analytical approach, the article explores three core dimensions of Sir Sayyid’s theology: his rational reinterpretation of Qur’anic exegesis in light of modern science, his critique of taqlid and advocacy for renewed ijtihad, and his project of harmonizing Islam with modernity. The analysis demonstrates that although pesantren exhibit institutional convergence with modern educational practices—particularly in integrating scientific knowledge—they maintain significant theological resistance at the metaphysical and epistemological levels. Pesantren selectively appropriate Sir Sayyid’s rationality as an instrumental epistemology while preserving Ashʿarite theology, the sacrality of revelation, and the authority of sanad. The findings suggest that Sir Sayyid’s modernist theology functions more as a catalytic reference than a doctrinal foundation within pesantren discourse. This study contributes to Islamic intellectual history by proposing a model of selective-epistemic adaptation and provides a theoretical framework for future empirical research on the reception of modernist Islamic thought in Indonesian pesantren.